PREFERENSI PETANI DALAM PEMANFAATAN DIGITAL MARKETING SEBAGAI SARANA PEMASARAN - Veralianta Br Sebayang; Doni Sahat Tua Manalu; Aditya Wicaksono; Suharno Suharno; Rasidin Karo Karo Sitepu (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2024)
The development of technology and information in the field of product marketing has become a challenge for all business actors, especially farmers, in marketing their products. This research aims to find out farmers' preferences in using digital marketing as a marketing tool. Study the case of the Okiagaru Marketing Cooperative. The sample was taken from 50 respondents who were members of the Okiagaru group. The analysis method uses Conjoint analysis. The results of the analysis show that the use of Digital Marketing is preferred by farmers with a level of interest in having broad and specific targets of 31.31%. Farmers also agree that promotional media using digital media is better than using Billboard/Spandak with an importance level of 25.15%. Marketing media is preferred using WEB sites and social media compared to market places with an importance level of 15.82%. Farmers prefer using cellphones or tablets compared to desktops with an interest level of 4.70%. To increase the target market, the strategies needed are (1) developing digital marketing applications based either on websites or social media, (2) increasing human resources such as transferring technological knowledge to the Okiagaru Marketing Cooperative